Penerapan Data Mining Klasifikasi Pada Calon Pelanggan Baru Indihome dengan C.45 - Arfandi Arfandi; Agus Perdana Windarto; Ilham Syahputra Saragih (Journal of Informatics, Electrical and Electronics Engineering, 2021)
Indihome customers are people who are buyers of products that have been made and marketed by a company, where this person not only buys the product once but repeatedly. Meanwhile, Prospective Indihome customers are those who have not become your customers (buyers/service users) but are considered to have the opportunity to become customers in the near future or in the future. An algorithm is needed to classify indihome's new prospective customers so that there is no loss between the two parties. The C4.5 algorithm was chosen because it is able to classify new prospective customers of Indihome by using the rapid miner application and the calculation using Microsoft Excel. From the calculations using the two applications, the results obtained include: If Income <2000000 and Type of House = Contract, then the result is Not Eligible {Eligible = 0 and Not Eligible = 7}and the result is feasible, namely the rule If Employment = Self Employed and Income> 2000000 then the result is Eligible (Eligible = 54 and Not Eligible = 0)